On the improvement of the rate of convergence of the generalized Bieberbach polynomials in domains with zero angles - Abdullayev, F.G.; Özkartepe, N.P. (Український математичний журнал, 2012)
Let ℂ be the complex plane, let C¯=C∪{∞}, let G ⊂ ℂ be a finite Jordan domain with 0 ∈ G; let L := ∂G; let Ω := C¯∖G¯, and let w = φ(z) be a conformal mapping of G onto a disk B(0, ρ₀) := {w:|w|<ρ₀} normalized by the conditions φ(z) = 0 and φ′(0)=1, where ρ₀ = ρ₀(0, G) is the conformal radius of G with respect to 0. Let